MEMILIH LINGKUNGAN PENDIDIKAN YANG BAIK BAGI ANAK - Samsul Bahri; Masdin Masdin; Pairin Pairin; Muh. Idris (Edukasi Islami: Jurnal Pendidikan Islam, 2014)
Choosing a good educational environment for children is the duty of parents to their children so that children can develop in line with expectations and activities of parents in the faith in God, because essentially every Muslim children are on the path toward God, while doing everything commanded by God, by degrees different. Furthermore, the parents are given the responsibility by God in order to have the ability to educate children to sacrifice life and property owned by the parents who will attempt the parents get multiple rewards from Allah if the parents do so with the intention of carrying out their faith in god. Parents should seek to know and understand the five human concept in Islam, namely the concept of al-Basyar, al-insan al-nas, the sons of Adam, and al-abid, opinions about factors related to the nature and environment of child development that is flow nativism, empiricism, convergent, jabariyah, Qadariyah, Islamic educational goals, and determine the Islamic educational environment for children.